Endoxifen, A new hope for Bipolar Disorder - Amin, Muneeba; Shafique, Alviya; Hafiz , Muhammad Yusuf (Journal of the Pakistan Medical Association, 2021)
Bipolar Disorder (BD), originally called manic depressive illness, is one of the most challenging and disabling psychiatric disorders to manage with an estimated life time prevalence of 1.02%. (1) One of the challenges is limitations in our understanding of the pathophysiology of the disorder which ultimately will lead to better treatment options. Despite available treatment options, literature reports breakthrough episodes in treated groups ranging from 40% to 60%. (2) This makes it even more crucial to gain more insight into the pathophysiology. Advances in molecular neuropsychiatry have reported that bipolar disorder is associated with overactive protein C kinase intracellular signaling. (3) Reportedly, lithium and valproate are protein C kinase inhibitors. Research has shown promise in effectiveness of Endoxifen. A multicenter, double-blind, active-controlled study was conducted using Endoxifen compared with Divalproex, the current standard treatment, in patients with BD. This new protein kinase C inhibitor has shown effectiveness in the treatment of acute mania and mixed mania. (4) One of the many advantages include similar efficacy as Divalproax without inducing thrombocytopenia and reportedly no need for drug monitoring due to wide therapeutic index is one of the reasons which results in decreased compliance. Additionally, it crosses the blood-brain barrier independent of CYP-2D6 metabolism. (4) With regards to disadvantages, cost effectiveness is a major hurdle. These new insights into pathophysiology and treatment options are crucial as till date BD remains one the most disabling mental health disorder affecting every aspect of life; individual, social, economic, global. BD is the fifth leading cause among psychiatric disorders of lost years of work. (5) It is therefore imperative that a new treatment is established and further research is warranted in regards to Endoxifen for better understanding to develop safe treatment, not only for management but possible cure. Continuous...